The Influence of Organizational Commitment and Organizational Satisfaction on Employee Productivity of The National Amil Zakat Board (BAZNAS) : (Literature Review of Human Resource Management) - Utama, Indra (The Eastasouth Management and Business, 2023)
Various efforts can be made by the organization, so that employees remain in the organization, including organizational commitment and satisfaction, because employees or workers who have both of these indicators will be loyal and have responsibility for what is their main function, which has an impact on increasing productivity. Work. This study aims to determine the effect of organizational commitment and organizational satisfaction on the work productivity of the employees of the National Amil Zakat Agency (Baznas). This research method is qualitative and literature review. The results of the analysis prove that: 1) Organizational comSmitment affects the work productivity of the National Amil Zakat Agency (Baznas) employees; 2) Organizational satisfaction affects the work productivity of the employees of the National Amil Zakat Agency (Baznas); 3) Organizational commitment and organizational satisfaction both affect the work productivity of the National Amil Zakat Agency (Baznas) employees.